Efek Financial Management Behavior, Self Efficacy, Herding Terhadap Keputusan Investasi Generasi Z (Effects of Financial Management Behavior, Self-Efficacy, Herding on Generation Z Investment Decisions) - Hidayat, Fikri; Siregar, Sandra Rosalie; Nugroho, Arif Widodo (Akutansi Bisnis & Manajemen ( ABM ), 2023)
This study was conducted to better understand the impact of financial management behavior, self-efficacy, and herding on the investment decisions of Generation Z. Those born between the years of 1997 and 2010, sometimes known as "Gen Z," are considered to be part of the "millennial" generation. The research used a purposive sample technique, whereby the data collected was tailored to meet certain criteria. Throughout the course of this survey, we were able to collect data from 153 individuals. Using Structural Equation Modeling (SEM) and the SmartPLS 3.0 software, we developed a method for doing in-depth statistical analysis. Research findings indicate that money management habits, self-efficacy, and herding all have a positive impact on investment decisions..